Fear of Wolves in Relation to Attacks on People and Livestock in Western Iran - Mohammadi, Alireza; Alambeigi, Amir; López-Bao, José V.; Kaboli, M. (Anthrozoös, 2021)
We evaluated local communities’ fear of wolves in a scenario of wolf attacks on people and livestock in Western Iran. In particular, we investigated the interaction between experiences of wolf attacks (both on people and livestock) and three factors: behavioral action (management action, e.g., livestock carcass management), religious (e.g., the belief that wolves can be a curse if harmed by humans), and cultural norms (e.g., village elders have taught their children not to kill or harm wolves). We surveyed 400 randomly chosen households throughout the villages located in Hamadan province, Iran. Participants (mean age = 48.5 years) reported experiences of wolf attacks on people and on livestock in 40% and 60% of interviews, respectively. The majority of the respondents were afraid of seeing a wolf in the wild (66.5%). The majority of interviewees abandoned their livestock carcasses near agricultural lands, rangelands, and rural areas. Our results suggest that cultural factors play an active role in allaying fear of wolves, and this influence occurs regardless of having or not having experiences of wolf attacks. However, experiences of wolf–livestock attacks did not have a meaningful role in decreasing or increasing the effect of culture, religion, and behavior on fear. Efforts to reduce human fear of wolves should consider minimizing risky encounters for people, particularly focusing on unsupervised children (<12 years old). Training programs on how to properly handle livestock carcasses (e.g., appropriate methods of disposal and not abandoning livestock carcasses close to human settlements) may reduce the frequency of wolf attacks. We thank the National Geographic Society who funded this research under the grant GEFNE128-14 and the UK Wolf Conservation Trust. J.V.L.B. was supported by a Ramon & Cajal research contract (RYC-2015-18932) from the Spanish Ministry of Economy, Industry, and Competitiveness.